Experimental investigation of a wildlife-safe origami-inspired reaction-type wind turbine for sustainable urban energy systems - Ahmad Sedaghat; Mohamad Hussein Farhat; Bassem Djedi; Mohamad Iyad Al-Khiami; Mohamed El Badawy (International Journal of Renewable Energy Development, 2026)
Small-scale wind turbines offer sustainable solutions for distributed renewable energy generation in urban environments. However, their deployment is often limited by concerns related to noise, visual impact, and risks to flying wildlife. This study presents an experimental investigation of a novel origami-inspired reaction-type wind turbine designed to improve urban compatibility through a compact, aesthetic, and bladeless configuration that enhances operational safety. Unlike conventional lift- or drag-based turbines, the proposed design operates based on a reaction force generated by redirecting axial inlet airflow into tangential outlet flow through internal nozzle conduits. Two miniature prototypes were fabricated using 3D printing with rotor diameters of 10 cm and 8 cm, both designed with a nozzle aspect ratio of unity and incorporating four inlet openings. The performance of the turbines was evaluated experimentally and theoretically under four operating conditions: free rotation, generator operation without load, fixed load operation, and variable load operation. Key performance parameters including cut-in wind speed, rotational speed, power output, and power coefficient were assessed through wind tunnel testing. The results demonstrate that the proposed origami wind turbine achieves a maximum power coefficient of C_P=0.28 at a tip speed ratio of λ=1.21, which is comparable to conventional small-scale turbines despite its bladeless configuration. Importantly, this study establishes that a reaction-type, bladeless turbine can simultaneously deliver competitive aerodynamic performance while significantly improving safety, reducing noise, and minimizing environmental impact. These findings highlight the strong potential of origami-inspired reaction-type wind turbines as viable and sustainable solutions for urban energy systems.